Mobile Equipment Tracking Based on Wi-Fi Technology: Case of An Open Pit Mine - Mazimba, Annie (Transactions on Engineering and Computing Sciences, 2024)
There are several positioning systems in the world which includes the commonly known GPS, GLONASS, BeiDou and Galileo. These happen to be satellite navigation systems. The paper presents a different approach of positioning using Wi-Fi access points. Most mobile equipment in open pit mines found in Zambia like Lumwana, Kalumbila and Kansanshi have Wi-Fi devices installed. These Wi-Fi enabled devices used for communication can be equally utilized for location tracking which would reduce on cost. In this study, three (3) access points were set up at 3 different locations in the line of sight of the mobile device. The access points provided the needed received signal strength indicator information (RSSI) for location tracking. A program to scan the RSSI information relevant to the position of the device was developed. Additionally, a server was configured to run mathematical computations that include distance estimations between the access point and the target device using the RSSI values received from the mobile device. The distance estimations were used for the trilateration. The trilateration gave the position estimation of the target device. The system results showed that RSSI measurements can be used to estimate the distance between the access point and the target device. Moreover, the coordinates from the trilateration were in the same range with the GPS coordinates.